Perovskite solar cell capable of improving crystal reduction defect and preparation method thereof
By using selenocyanate as an additive in perovskite solar cells to regulate crystallization and passivate defects, the problems of insufficient crystallinity and many defects in perovskite solar cells are solved, high-efficiency device preparation and improved stability are achieved, which is conducive to industrialization.
Patent Information
- Application Number
- CN202510663595.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-10-10
AI Technical Summary
Existing perovskite solar cells have problems with insufficient crystallinity and many defects during the preparation process, which affects device performance and stability and hinders their commercial development.
Selenium cyanate is used as an additive to regulate the crystallization of perovskite, passivate defects, inhibit non-radiative recombination, enhance carrier transport, and prepare perovskite solar cells with improved crystallization.
The crystallization quality and performance of perovskite solar cells have been significantly improved, and high-efficiency device preparation has been achieved, which is conducive to industrialization and large-scale application.
Smart Images

Figure CN120769650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite solar cell with improved crystallization and reduced defects and a preparation method thereof. Background Art
[0002] Perovskite solar cells can generate electricity from solar energy, with the photoelectric conversion efficiency of small-area devices exceeding 26%. The preparation of high-performance perovskite solar cells will facilitate their commercialization. Most existing reports on perovskite solar cells are prepared in nitrogen, which requires high equipment requirements, increases manufacturing costs, and involves complex experimental procedures, making it unsuitable for large-scale production. While some inventions have been developed to prepare perovskites in atmospheric air, their crystallinity still has significant room for improvement. Furthermore, defects in perovskites can reduce device performance and stability, hindering their large-scale and long-term application. During the perovskite crystallization process, defects form within the perovskite grains and at their boundaries, reducing device performance and stability and hindering the commercialization of perovskite devices. Therefore, the use of appropriate additives to control perovskite crystallization, improve the crystalline quality of the perovskite active layer, and passivate defects can help improve device performance and stability. Currently, patents using these additives exist, such as patent CN119012880A, which uses guanidine thiocyanate to improve perovskite crystallinity, and patent CN118946172A, which uses formamidine thiocyanate to increase perovskite grain size. However, the research in these patents is not thorough enough and has limited effect on improving the quality of perovskite crystals. Patent CN119403419A uses selenocyanate to regulate perovskite crystallization, but does not further investigate defect passivation, non-radiative recombination intensity, and carrier transport in perovskites. Summary of the Invention
[0003] The present invention aims to address at least one of the technical problems existing in the related art. To this end, the present invention provides a perovskite solar cell with improved crystallization and reduced defects, and a method for preparing the same. The invention uses selenocyanate (SeCN) to dope the perovskite, regulating its crystallization and improving its quality. Selenocyanate can passivate defects in the perovskite, inhibiting non-radiative recombination, facilitating carrier transport, and improving device performance. This enables the preparation of high-efficiency perovskite solar cells, facilitating industrialization and large-scale application.
[0004] The present invention provides a perovskite solar cell with improved crystallization and reduced defects, comprising a fluorine-doped tin oxide conductive glass substrate layer, an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode layer stacked in sequence. The perovskite active layer includes selenocyanate, and the selenocyanate includes potassium selenocyanate, sodium selenocyanate, and cesium selenocyanate.
[0005] Furthermore, the thickness of the perovskite active layer is 500nm~800nm.
[0006] The application discloses a preparation method of a perovskite solar cell with improved crystallization and reduced defects. S1. Ultrasonic cleaning of a fluorine-doped tin oxide conductive glass substrate in air, and drying with nitrogen; S2. Spin coating of a colloidal tin dioxide aqueous solution on the fluorine-doped tin oxide conductive glass substrate layer in air, forming an electron transport layer through first annealing; S3. Adding selenocyanate to a perovskite precursor solution, spin coating on the surface of the electron transport layer, dropwise adding an anti-solvent, and forming a perovskite active layer through second annealing; S4. Spin coating of a Spiro-OMeTAD solution on the perovskite active layer in air, forming a hole transport layer; S5. Vacuum evaporation of a metal electrode layer on the surface of the hole transport layer, obtaining a perovskite solar cell.
[0007] Further, the first annealing temperature is 90-180 DEG C, and the first annealing time is 20-60 min; The second annealing temperature is 25-150 DEG C, and the second annealing time is 10-30 min.
[0008] Further, the mass concentration of the colloidal tin dioxide aqueous solution is 2-5%, and the anti-solvent is a non-polar solvent.
[0009] Further, the perovskite precursor solution comprises cesium iodide, methylamine bromide, methylamine chloride, lead bromide, formamidinium iodide and lead iodide, is dissolved in solvent 1, and selenocyanate is added to the solvent 1.
[0010] Further, the concentration of the selenocyanate is 1-5 mg / ml, and the selenocyanate is used as a defect passivation agent to improve crystallization and passivate defects.
[0011] Further, the solvent 1 is a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1.
[0012] Further, the Spiro-OMeTAD solution is a chlorobenzene solution of Spiro-OMeTAD, and lithium bistrifluoromethylsulfonylimide / acetonitrile solution and tert-butylpyridine are added.
[0013] Further, the thickness of the metal electrode layer is 50-150 nm, and the material of the metal electrode is gold or silver.
[0014] The one or more technical solutions in the embodiments of the application have at least one of the following technical effects: By using selenocyanate as an additive, the perovskite crystallinity is improved, the perovskite active layer crystalline quality is optimized, and the perovskite solar cell is rapidly prepared in air, selenocyanate as a defect passivation agent, significantly reduces the defects in perovskite, inhibits non-radiative recombination, is conducive to carrier transport, and improves the performance of the device, so as to realize the preparation of high-efficiency perovskite solar cells, which is conducive to industrialization and large-scale application.
[0015] Additional aspects and advantages of the application will be set forth in part in the description which follows, and in part will become apparent to those skilled in the art upon examination of the following description, or can be learned by practice of the application. BRIEF DESCRIPTION OF DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description are some embodiments of the application, and those skilled in the art can also obtain other drawings according to these drawings without creative labor.
[0017] Figure 1 It is a structure schematic diagram of the perovskite solar cell for improving crystallization and reducing defects provided by the application.
[0018] Figure 2 It is a scanning electron microscope graph of the perovskite active layer doped with potassium selenocyanate and the perovskite active layer without doping potassium selenocyanate provided by the application.
[0019] Figure 3 It is an X-ray diffraction graph of the perovskite active layer of experimental example 2 and the perovskite active layer without doping potassium selenocyanate before annealing provided by the application.
[0020] Figure 4 It is a steady-state photoluminescence spectrum graph of the perovskite active layer of experimental example 2 and the perovskite active layer without doping potassium selenocyanate provided by the application.
[0021] Figure 5 It is a transient photoluminescence spectrum graph of the perovskite active layer of experimental example 2 and the perovskite active layer without doping potassium selenocyanate provided by the application.
[0022] Figure 6 The scanning electron microscope graph of the experimental example and the comparative example of the application. DETAILED DESCRIPTION
[0023] In order to make the objects, technical solutions and advantages of the present application clearer, the technical solutions in the present application will be clearly and completely described below. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of the present application. The following embodiments are used to illustrate the present application, but cannot be used to limit the scope of the present application.
[0024] In the description of the embodiments of the present application, it should be noted that the terms "first", "second", "third" are only used for descriptive purposes, and cannot be understood or implied as indicating or implying relative importance. In the description of the present application, the description of the terms "one embodiment", "some embodiments", "an example", "a specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiments of the present application. In the present application, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples. In addition, those skilled in the art can combine and combine the different embodiments or examples described in the present application and the features of the different embodiments or examples without contradiction.
[0025] The following will be described in conjunction with Figures 1 to 6 An improved crystalline defect-reducing perovskite solar cell and a preparation method thereof are described.
[0026] As Figure 1 shown, an improved crystalline defect-reducing perovskite solar cell, includes a fluorine-doped tin oxide (FTO) conductive glass substrate layer, an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode layer which are sequentially stacked; the perovskite active layer includes selenocyanate, and the selenocyanate includes potassium selenocyanate, sodium selenocyanate and cesium selenocyanate.
[0027] The thickness of the perovskite active layer is 500-800 nm.
[0028] A preparation method of an improved crystalline defect-reducing perovskite solar cell is used to prepare the above-mentioned improved crystalline defect-reducing perovskite solar cell, comprising: S1: ultrasonic cleaning the FTO conductive glass substrate in air, and drying with nitrogen; Specifically, the FTO conductive glass substrate is ultrasonically cleaned in air, and dried with nitrogen, and the FTO conductive glass substrate is treated with ultraviolet ozone.
[0029] S2: A colloidal tin dioxide (SnO2) aqueous solution is spin-coated on the fluorine-doped tin oxide transparent conductive glass substrate layer in air, and an electron transport layer is formed by first annealing; Specifically, the SnO2 colloidal aqueous solution is spin-coated on the fluorine-doped tin oxide conductive glass substrate, and placed on a hot stage to obtain the electron transport layer by first annealing, wherein the mass concentration of the SnO2 colloidal aqueous solution is 2% to 5%, preferably 3.75%; the first annealing temperature is 90°C to 180°C, preferably 150°C; and the annealing time is 20 minutes to 60 minutes, preferably 30 minutes.
[0030] S3: In air, selenocyanate is added to the perovskite precursor solution and spin-coated on the surface of the electron transport layer to form a perovskite active layer by second annealing; Specifically, the perovskite precursor solution comprises cesium iodide (CsI), methylamine bromide (MABr), methylamine chloride (MACl), lead bromide (PbBr2), formamidinium iodide (FAI) and lead iodide (PbI2), and is dissolved in solvent 1, and a certain concentration of selenocyanate additive is added to the above prepared solution to obtain a precursor solution doped with different concentrations. The precursor solution is spin-coated on the FTO conductive glass substrate layer, and an appropriate amount of anti-solvent is added, and then second annealing is immediately performed to obtain the perovskite active layer.
[0031] The contents of cesium iodide, methylamine bromide, methylamine chloride, lead bromide, formamidinium iodide and lead iodide are 0.068 mol / L cesium iodide, 0.044 mol / L methylamine bromide, 0.444 mol / L methylamine chloride, 0.044 mol / L lead bromide, 1.465 mol / L formamidinium iodide and 1.594 mol / L lead iodide, respectively.
[0032] The solvent 1 is a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1. The anti-solvent is a non-polar solvent, preferably chlorobenzene; The second annealing temperature is 90°C to 150°C, preferably 100°C, and the concentration of the selenocyanate additive is 1-5 mg / ml.
[0033] S4: In air, a 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) solution is spin-coated on the perovskite active layer to form a hole transport layer; Specifically, the hole transport layer is obtained by spin-coating a Spiro-OMeTAD solution on the surface of the perovskite active layer. The Spiro-OMeTAD solution is a chlorobenzene solution of Spiro-OMeTAD, and lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI) / acetonitrile solution and tert-butylpyridine (tBP) are added.
[0034] S5: vacuum evaporation of a metal electrode layer on the surface of the hole transport layer to obtain a perovskite solar cell.
[0035] Specifically, the thickness of the metal electrode is 50-150 nm, preferably 80 nm; the material of the metal electrode can be gold or silver.
[0036] The experimental examples of the application are all taken as potassium selenocyanate (KSeCN) as an example.
[0037] Experimental Example 1 The FTO conductive glass substrate was immersed in deionized water and anhydrous ethanol for ultrasonic cleaning for 15 min, and then dried with nitrogen. The FTO conductive glass substrate was subjected to ultraviolet ozone treatment and was ready for use.
[0038] Preparation of the electron transport layer: SnO2 colloid aqueous solution with a mass concentration of 3.75% was spin-coated on the FTO conductive glass substrate at a speed of 3000 rpm for 30 s. The spin-coated FTO conductive glass substrate was placed on a hot stage and annealed at 150℃ for 30 min (first annealing), and then cooled to room temperature. The spin-coating and annealing were performed in air.
[0039] Preparation of the perovskite active layer: CsI (17.7 mg), MABr (4.9 mg), MACl (30.0 mg), PbBr2 (16.1 mg), FAI (251.9 mg), and PbI2 (734.9 mg) were dissolved in a mixed solvent of DMF (800 μL) and DMSO (200 μL) and stirred to dissolve. 1 mg of potassium selenocyanate was added to the above solution and stirred to dissolve, obtaining a perovskite precursor solution. The perovskite precursor solution was spin-coated on the electron transport layer at a speed of 6000 rpm for 30 s. 2 mL of chlorobenzene (anti-solvent) was quickly added at the last 7 s of the spin-coating process, and then placed on a hot stage for second annealing at a temperature of 150℃ for 30 min, obtaining a black perovskite film, i.e. the perovskite active layer. The spin-coating was performed in ambient air.
[0040] Preparation of the hole transport layer: Spiro-OMeTAD (72 mg) was dissolved in 1 mL of chlorobenzene, and 28.5 μL of tBP and 18 μL of Li-TFSI acetonitrile solution (520 mg / mL) were added. The prepared solution was spin-coated on the surface of the perovskite active layer at a speed of 3000 rpm for 30 s to form a hole transport layer. The spin-coating was performed in ambient air.
[0041] The Ag is evaporated to the surface of the hole transport layer under high vacuum degree by using a vacuum evaporation device, and a metal electrode with a thickness of 80 nm is deposited.
[0042] Experimental Example 2: Compared with Experimental Example 1, the difference of the present experimental example is that 1 mg of potassium selenocyanate is replaced by 2 mg of potassium selenocyanate, and the rest is the same, which will not be repeated here.
[0043] Experimental Example 3: Compared with Experimental Example 1, the difference of the present experimental example is that 1 mg of potassium selenocyanate is replaced by 5 mg of potassium selenocyanate, and the rest is the same, which will not be repeated here.
[0044] Comparative Example: Compared with Experimental Example 1, the difference of the present experimental example is that 1 mg of potassium selenocyanate is not added, and the rest is the same, which will not be repeated here.
[0045] As Figure 2 shown in the scanning electron microscope images of the perovskite active layer doped with potassium selenocyanate and the perovskite active layer without doping potassium selenocyanate, as Figure 2 shown in (a) of the figure, the perovskite active layer without potassium selenocyanate has more grain boundaries on the surface. As Figure 2 shown in (b) of the figure, the perovskite active layer after doping potassium selenocyanate in the perovskite, the perovskite grain increases significantly, and the crystalline quality is improved. Large grains indicate that there are fewer grain boundaries in the perovskite, and there are a large number of defects in the grain boundaries. Therefore, after doping potassium selenocyanate, there are fewer defects in the perovskite, which is beneficial to the preparation of high-efficiency devices.
[0046] As Figure 3 shown in the X-ray diffraction images of Experimental Example 2 of the present application and the perovskite active layer before annealing without doping potassium selenocyanate. Among them, the alpha phase is a photoactive phase that can convert light energy into electrical energy; the diffraction intensity of the perovskite alpha phase doped with potassium selenocyanate is larger, and there is no lead iodide peak, indicating that potassium selenocyanate significantly enhances the crystallinity of the perovskite, improves the crystalline quality of the perovskite, and improves the phase purity of the photoactive phase, which is beneficial to the preparation of high-efficiency devices. Figure 3 (b) of the figure, as Figure 3 (a) of the figure, as Figure 3 (b) of the figure, the peak position of the 14-degree peak does not change significantly, indicating that the selenocyanate does not enter the perovskite lattice to replace the halogen ion, as a same group element, O 2- , S 2- , Se 2-The ionic radii are 140 pm, 184 pm, and 198 pm, respectively. Halogen ions with similar radii can replace each other, such as oxycyanate (OCN) (radius 197 pm) replacing bromide (radius 195 pm), and thiocyanate (SCN) (radius 217 pm) replacing iodide (radius 220 pm). However, selenocyanate, with a significantly larger radius than thiocyanate, cannot replace iodide into the crystal lattice. It acts as a volatile additive during crystallization and is removed after annealing.
[0047] like Figure 4 The steady-state photoluminescence spectra of the perovskite active layer of Experimental Example 2 of the present invention and the perovskite active layer not doped with potassium selenocyanate are shown. After doping with potassium selenocyanate, the photoluminescence intensity of the perovskite is significantly enhanced, indicating that non-radiative recombination is suppressed and there are fewer defects in the perovskite.
[0048] like Figure 5 Figures show the transient photoluminescence spectra of the perovskite active layer from Experimental Example 2 of the present invention and that from an undoped perovskite. Doping with potassium selenocyanate significantly increases the fluorescence lifetime of the perovskite. Table 1 shows the lifetime fitting parameters for the transient photoluminescence spectra of the perovskite active layer without and with potassium selenocyanate. As shown in Table 1, the average lifetime increases from 679.4 ns to 1237.1 ns. This long average carrier lifetime indicates that non-radiative recombination is suppressed and defects in the perovskite are passivated by potassium selenocyanate.
[0049] Table 1 Lifetime fitting parameters of transient photoluminescence spectra of perovskite active layer without and with potassium selenocyanate Wherein A1 is the first attenuation coefficient, A2 is the second attenuation coefficient, t1 is the first attenuation time, t2 is the second attenuation time, and t is the calculated average carrier lifetime.
[0050] Table 2 Parameters of perovskite solar cells of comparative examples and experimental examples Table 2 is the parameters of the perovskite solar cells of the comparative examples and experimental examples, in Table 2, the open-circuit voltage (Voc) refers to the potential difference between the two ends of the circuit when the current in the circuit is zero or the external load impedance is infinite, and the intersection value of the J-V curve and the x-axis is the value of the open-circuit voltage. The degree of energy level matching between the perovskite layer and the transport layer affects the size of the open-circuit voltage. The short-circuit current density (Jsc) refers to the ratio of the current in the circuit to the unit cross-sectional area when the voltage in the circuit is zero or the external load is infinite, and the intersection value of the J-V curve and the y-axis is the value of the short-circuit current. The substrate transmittance, the band gap of the perovskite, the quality of the perovskite film, the film thickness, and the interface contact with the transport layer jointly affect the short-circuit current density. The fill factor (FF) is the ratio of the maximum output power of the battery device to the product of the short-circuit current and the open-circuit voltage. The interface contact of each functional layer of the device affects the series and parallel resistances, and then affects the fill factor. The larger the FF, the closer the J-V curve to the rectangle. The power conversion efficiency (PCE) is the ratio of the maximum output power of the battery device to the incident light power, that is, the photoelectric conversion efficiency. PCE is a direct parameter to measure the performance of the device.
[0051] As shown in Table 2, the device efficiency of the experimental example 1, the experimental example 2, the experimental example 3 and the comparative example perovskite solar cells was tested under the simulated sunlight condition of AM1.5G 100mW•cm -2 As shown in Table 2, the device efficiency of the experimental example 1, the experimental example 2, the experimental example 3 and the comparative example perovskite solar cells was tested under the simulated sunlight condition of AM1.5G 100mW•cm 2 The conversion efficiency of the experimental example 1, the experimental example 2 and the experimental example 3 is significantly higher than that of the comparative example, wherein the conversion efficiency of the experimental example 1 is the highest, which is 24.96%, the conversion efficiency of the experimental example 2 is the best, which can be up to 25.74%, the conversion efficiency of the experimental example 3 is the highest, which is 24.40%, and the conversion efficiency of the comparative example is the highest, which is 23.65%. It can be seen that the conversion efficiency of the experimental example 1, the experimental example 2 and the experimental example 3 is significantly higher than that of the comparative example.
[0052] As shown in Figure 6 , the surface morphology of the perovskite of the experimental example 1, the experimental example 2, the experimental example 3 and the comparative example was tested by scanning electron microscope. As shown in Figure 6 (a) of the figure, the perovskite crystal grains of the comparative example are small, and the average size is about 600nm. As shown in Figure 6 (b) of the figure, the experimental example 1 and as shown in Figure 6The perovskite grains of the experimental example 2 in Fig. (c) are significantly increased, wherein the grains of the experimental example 1 can reach more than 1 μm, and the grains of the experimental example 2 can reach more than 2 μm. It is shown that potassium selenocyanate can reduce grain boundaries, improve perovskite quality, and thus reduce defects in perovskite. For example Figure 6 The grains of the experimental example 3 in Fig. (d) are slightly increased due to excessive addition of potassium selenocyanate.
[0053] The present application improves perovskite crystallinity by using selenocyanate as an additive, optimizes perovskite active layer crystalline quality, and realizes rapid preparation of perovskite solar cells in air. Selenocyanate as a defect passivation agent significantly reduces defects in perovskite, suppresses non-radiative recombination, is conducive to carrier transport, and improves device performance, thereby realizing the preparation of high-efficiency perovskite solar cells and being conducive to industrialization and large-scale application.
[0054] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, and not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A perovskite solar cell with improved crystallization and reduced defects, characterized in that: It includes a fluorine-doped tin oxide conductive glass substrate layer, an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode layer stacked in sequence. The perovskite active layer includes selenocyanate, and the selenocyanate includes potassium selenocyanate, sodium selenocyanate, and cesium selenocyanate.
2. The perovskite solar cell with improved crystallization and reduced defects according to claim 1, characterized in that: The thickness of the perovskite active layer is 500nm~800nm.
3. A method for preparing a perovskite solar cell with improved crystallization and reduced defects, characterized in that: For preparing a perovskite solar cell with improved crystallization and reduced defects as claimed in any one of claims 1 to 2, comprising: S1: Ultrasonic cleaning of the fluorine-doped tin oxide conductive glass substrate in air and drying with nitrogen; S2: In air, spin-coating a tin dioxide colloidal aqueous solution onto a fluorine-doped tin oxide conductive glass substrate layer, followed by a first annealing step to form an electron transport layer; S3: In air, selenocyanate is added to the perovskite precursor solution, spin-coated on the surface of the electron transport layer, and an anti-solvent is added dropwise. The perovskite active layer is formed by a second annealing step. S4: In air, the Spiro-OMeTAD solution is spin-coated on the perovskite active layer to form a hole transport layer. S5: forming a metal electrode layer by vacuum evaporation on the surface of the hole transport layer to obtain a perovskite solar cell.
4. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 3, characterized in that: The first annealing temperature is 90°C~180°C, and the first annealing time is 20min~60min; The second annealing temperature is 90° C. to 150° C., and the second annealing time is 10 min to 30 min.
5. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 3, characterized in that: The mass concentration of the tin dioxide colloidal aqueous solution is 2% to 5%, and the anti-solvent is a non-polar solvent.
6. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 3, characterized in that: The perovskite precursor solution comprises cesium iodide, methylammonium bromide, methylammonium chloride, lead bromide, formamidine iodide and lead iodide, which are dissolved in solvent 1, and selenocyanate is added to solvent 1.
7. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 6, characterized in that: The concentration of the selenocyanate is 1 mg / ml to 5 mg / ml. The selenocyanate is used as a defect passivating agent to improve crystallization and passivate defects.
8. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 6, characterized in that: The solvent 1 is a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:
1.
9. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 3, characterized in that: The Spiro-OMeTAD solution is a chlorobenzene solution of Spiro-OMeTAD, and a lithium bis(trifluoromethylsulfonyl)imide / acetonitrile solution and tert-butylpyridine are added.
10. The method for preparing a perovskite solar cell with improved crystallization and reduced defects according to claim 3, characterized in that: The thickness of the metal electrode layer is 50nm-150nm, and the material of the metal electrode layer is gold or silver.